Managing water through change and uncertainty: comparing lessons from the adaptive co-management literature to recent policy developments in England - Whaley, Luke; Weatherhead, E. K. (Taylor and Francis, 2015)
Abstract Water management is set to become increasingly variable and unpredictable, in particular because of climate change. This paper investigates the extent to which water policy in England provides an enabling environment for ‘adaptive co-management’, which its proponents claim can achieve the dual objective of ecosystem protection and livelihood sustainability under conditions of change and uncertainty. Five policy categories are derived from a literature review, and are used to conduct a directed content analysis of seven key water policy documents. The findings reveal that although, in part, English water policy serves as an enabling environment for adaptive co-management, there is a level of discrepancy between substantive aspects of the five policy categories and water policy in England. Addressing these discrepancies will be important if English water policy is to allow for the emergence of processes, like adaptive co-management, that are capable of coping with the challenges that lie ahead
Keywords: adaptive co-management; policy; water governance; England